Solution Equilibrium Studies on Metal(II) Complexes with 3-Amino-2-benzofurancarboxamide Schiff Base - Halli, M.B.; Mallikarjun, Kinni.; B. Patil, Vijayalaxmi.; Sumathi, R.B. (Asian Journal of Chemistry, 2011)
The stability constant of Cu(II), Ni(II), Co(II), Cd(II), Ba(II), Mg(II) and UO2(II) complexes were determined with Schiff base derived from condensation of 3-amino-2-benzofurancarboxamide with 8-formyl-7-hydroxy-4-methyl-coumarin by pH metric method. Irving-Rossotti technique was used to determine pKHOH and log K values, at constant ionic strength of 0.1M NaNO3 at 30 ± 1 °C in 60:40 % (v/v) alcohol and water medium. The order of stability constant was found to be UO2 > Cu > Ni > Cd > Co > Ba > Mg. The negative values of free energy change suggest that the reactions are spontaneous one.